Przyczyny problemów z szacowaniem wartości informacji - Cypryjański, Jacek (Causes of the Difficulties in Assessing Value of Information, 2005)
The paper discusses five causes of the difficulties in assessing value of information: necessity of using value XXX; the fact that one information can be utilized in the same time, by many users for realization of different tasks; existence of the information asymmetry phenomenon; difficulties in defining information quality; difficulties in presenting information in the form of discrete random variable with known probability distribution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 14-20